If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -6) + -9 = -3(-8x + 7) + -5x Reorder the terms: 3(-6 + x) + -9 = -3(-8x + 7) + -5x (-6 * 3 + x * 3) + -9 = -3(-8x + 7) + -5x (-18 + 3x) + -9 = -3(-8x + 7) + -5x Reorder the terms: -18 + -9 + 3x = -3(-8x + 7) + -5x Combine like terms: -18 + -9 = -27 -27 + 3x = -3(-8x + 7) + -5x Reorder the terms: -27 + 3x = -3(7 + -8x) + -5x -27 + 3x = (7 * -3 + -8x * -3) + -5x -27 + 3x = (-21 + 24x) + -5x Combine like terms: 24x + -5x = 19x -27 + 3x = -21 + 19x Solving -27 + 3x = -21 + 19x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-19x' to each side of the equation. -27 + 3x + -19x = -21 + 19x + -19x Combine like terms: 3x + -19x = -16x -27 + -16x = -21 + 19x + -19x Combine like terms: 19x + -19x = 0 -27 + -16x = -21 + 0 -27 + -16x = -21 Add '27' to each side of the equation. -27 + 27 + -16x = -21 + 27 Combine like terms: -27 + 27 = 0 0 + -16x = -21 + 27 -16x = -21 + 27 Combine like terms: -21 + 27 = 6 -16x = 6 Divide each side by '-16'. x = -0.375 Simplifying x = -0.375
| 5x+4-7x=5x-13 | | G-1=7 | | -9x+2=-3(3x+2) | | -26=6(v-6)-8v | | x/4+10=-2 | | 12=y+4 | | 6x-4=2x+28 | | 3xsquared-150x-1200=600 | | -13.00x+2.00=8 | | E+6-1=3 | | 2.3=4.5X+30.2 | | -13.00+2.00=8 | | y=15x+27 | | 0.05-0.6x=5.3 | | (2ax+bx)(2ax+bx)= | | R-3.5=-2.1 | | 15=5+y | | 32x^3+13x^3+23x^4= | | 32x^3+13x^3+13x^3= | | 8x-9=3x+-16 | | 6[x+4]=36 | | 6(-17-3y)+2y=10 | | (x+2y)2= | | mx^2+(m-1)x-3=0 | | 130+2x+10=180 | | 4b+7=1b+15 | | 13/19+6y=9 | | 3x^2-27x-30=0 | | 2(x+2)=2x | | 51x^5+119x^9+221x^10= | | 12a+11b+2c+4c-5b-2a= | | -10+7y+6y=9 |